The Impact of Intellectual Capital on Financial Performance of Insurance Firms in Tanzania (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2024)
This paper investigated the impact of intellectual capital on the financial performance of insurance companies in Tanzania. The study used data collected from eleven (11) insurance companies from 2009 to 2018. A random effect panel regression model was used to estimate the impact of the two measures of intellectual capital, namely human capital efficiency and structural capital efficiency. We controlled for the differences in leverage and capital employed. The findings show that human capital efficiency positively and significantly influences financial performance. However, we did not find any evidence regarding the influence of structural capital on financial performance. The findings of this study imply that for any firm to excel financially, it must explore and utilise its internal capabilities, especially human and physical capital, in the best way possible.